Hyper-hyponymic paradigm of “clothing” in English - Kabulova, Gulruxsor (The Lingua Spectrum, 2025)
This article is devoted to the study of the hyponim-hyperonimic paradigm of “clothing” in English. It presents a semantic analysis of the hyper-hyponymic paradigm of clothing and footwear in the English language. It explores lexical units denoting women’s, men’s, and unisex clothing, with a focus on structural features (shoulder, waist), usage (casual, sportswear), and seasonal relevance (summer, winter, all-season). The study reveals a high frequency of casual and multifunctional items, reflecting the cultural tendency toward versatility and comfort in English-speaking societies. Special attention is given to the rise of unisex fashion and the functional role of accessories. The paradigm’s hierarchical structure is analyzed through microfields, demonstrating overlapping semantic features and fluid category boundaries. Additionally, the paper highlights a group of terms actively used in professional and colloquial contexts but absent in dictionaries, reflecting the dynamic evolution of fashion-related vocabulary. Findings underscore the importance of cultural and linguistic factors in clothing nomenclature and support the global trend toward gender neutrality and practical fashion.